2000
DOI: 10.1902/jop.2000.71.2.219
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Scanning Electron Microscopic Study on the Characteristics of Demineralized Dentin Root Surface Using Different Tetracycline HCl Concentrations and Application Times

Abstract: Dentin demineralization is not time dependent at all concentrations of tetracycline HCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 32 publications
5
65
0
10
Order By: Relevance
“…Several previous studies that have assessed the effects of EDTA gel as a coadjuvant in periodontal treatment focused on the root surface of human teeth extracted due to severe periodontitis. The purpose of these studies was to analyze the surface topography of periodontally affected human tooth roots after application of EDTA gel with different combinations of treatments (4,5,7,12,(16)(17)(18)29,30). The authors concluded that root surfaces treated with EDTA appeared to be more suitable for cellular colonization and subsequent connective tissue formation (4,5), and exhibited numerous dentinal tubules exposed by removal of the smear layer (7,12,16,17,29), and an intact collagenous matrix (18,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies that have assessed the effects of EDTA gel as a coadjuvant in periodontal treatment focused on the root surface of human teeth extracted due to severe periodontitis. The purpose of these studies was to analyze the surface topography of periodontally affected human tooth roots after application of EDTA gel with different combinations of treatments (4,5,7,12,(16)(17)(18)29,30). The authors concluded that root surfaces treated with EDTA appeared to be more suitable for cellular colonization and subsequent connective tissue formation (4,5), and exhibited numerous dentinal tubules exposed by removal of the smear layer (7,12,16,17,29), and an intact collagenous matrix (18,30).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widely used agents for this purpose is citric acid (9). However, other agents such as tetracycline (10)(11)(12) and ethylenediaminetetraacetic acid (EDTA) (6,13,14) have also been employed.…”
Section: Introductionmentioning
confidence: 99%
“…Samples in the groups II, III, IV and V were conditioned during 3 minutes and solutions were renewed every 30 seconds. [18][19][20] After the conditioning procedure samples were washed with 10 ml of saline solution.…”
Section: Conditioning Proceduresmentioning
confidence: 99%
“…Thus, the more open dentin tubuli is, the more clean root canal walls of the smear layer. [21][22][23] SEM was chosen because this tool can be a b c d e figure 1. SEM photograph of the surface rootcanals in group: a) control: the entire root canal walls were covered with non-homogeneous smear layer (heavy), (b) 10% red betel leaf infusion: the entire root canal walls were covered with homogeneous smear layers, c) 20% red betel leaf infusion: the entire root canal walls were covered with homogeneous smear layers, d) 30% red betel leaf infusion: there was no smear layer, and all dentin tubuli were open and clean, e) 40% red betel leaf infusion: there was no smear layer, and all dentin tubuli were open and clean.…”
Section: -4mentioning
confidence: 99%